Eksistensi Penentuan Kerugian Negara Dalam Penyidikan Tindak Pidana Korupsi - Bagus Priyo Atmojo (UNISSULA Semarang, 2017)
State losses are one of the elements that must exist in the criminal act of corruption in the core sense other than other corrupt acts such as gratification. The element of state losses is a fundamental element other than the element of the legal subject of corruption. For that state losses become one of the attention in handling corruption crime. Investigators as the spearhead in criminal law enforcement are those who have the duty and responsibility of conducting an investigation to determine the state losses as well as to find the suspect and how the criminal act of corruption is done and other matters concerning it.The criminal act of corruption in the perspective of positive law is an act that has a fundamental element of state losses. As in the perspective of Islamic Law a criminal act of corruption is a prohibited act or is an act of haram. Determination of state losses has an important existence. State losses are one of the main elements of corruption that must be proven. This causes the determination of losses of the state has a central position for whether or not criminal acts of corruption are prosecuted. Mistakes in determining state losses can lead to failure in law enforcement against corruption.It is necessary to stipulate the party that can determine the state losses other than the CPC and BPKP as mentioned in the Constitutional Court Decision Number 31 / PUU-X / 2012 dated October 23, 2012 due to the provisions on the agency and other parties (including from the company), which may indicating material truth in the calculation of state losses and / or may prove the case in hand as stated in the Constitutional Court ruling the scope is still too wide.Keywords: Existence, State Loss, Corruption